Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1034/j.1600-0587.2002.250207.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of forest edge on populations of white‐footed mice Peromyscus leucopus

Abstract: Several studies have reported higher densities of white‐footed mice in small fragments than in large fragments of eastern deciduous forests. The edge hypothesis states that higher densities in smaller fragments reflect an increase in relative amount of edge habitat, which supports higher densities of mice because of its higher quality. To test this hypothesis we live trapped white‐footed mice along edge‐to‐interior gradients in forest fragments of east‐central Illinois. Our results indicated a greater abundanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 31 publications
0
23
1
1
Order By: Relevance
“…However, other studies found contrasting results to those reported here. For example, a study of the whitefooted mouse determined that abundance was greatest in the forest interior rather than in the edge in an agricultural landscape (Wolf and Batzli 2002). Abundance of small mammals may be affected by variables at the microclimate scale, such as resource availability, abundance of predators and parasites, and presence of understory woody debris (Bellows et al 2001;Wolf and Batzli 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies found contrasting results to those reported here. For example, a study of the whitefooted mouse determined that abundance was greatest in the forest interior rather than in the edge in an agricultural landscape (Wolf and Batzli 2002). Abundance of small mammals may be affected by variables at the microclimate scale, such as resource availability, abundance of predators and parasites, and presence of understory woody debris (Bellows et al 2001;Wolf and Batzli 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Al though other fac tors could con trib ute to vari a tion in the rel a tive abun dance of P. leucopus in for est patches (eg, com pe ti tion, pre dation, ac cess to ma trix; see Mac Ar thur et al 1972, Nupp and Swihart 1998, Wolf and Batzli 2002, our re sults strongly sup port the hy poth e sis that greater struc tural com plex ity of understory vege ta tion re sults in a greater rel a tive abun dance of P. leucopus. This ap pears to be in con trast to Wolf and Batzli (2004) who found that for est "edge" hab i tat was of rel a tively poor qual ity; however, they de fined "edge" hab i tat as be ing 5 times wider in their study.…”
Section: Discussionmentioning
confidence: 99%
“…Los diversos procesos asociados que inciden sobre las dinámicas y condiciones que tienen lugar en los fragmentos son conocidos como "efecto borde" (MURCIA, 1995;LAURANCE, 1997;WOLF Y BATZLI, 2002;DESROCHERS ET AL., 2003;SCHTICKZELLE Y BAGUETTE, 2003).…”
Section: Ii2 Efecto Borde Sobre Los Fragmentos De Hábitatunclassified